Neuro-Behavioral Status and the Hippocampal Expression of Metabolic Associated Genes in Wild-Type Rat Following a Ketogenic Diet - Ling, Ya; Wang, Dan-dan; Sun, Yu-xiao; Zhao, Dong-jing; Ni, Hong (Frontiers in Neurology, 2019)
Clinical evidence of relevant adverse events of a a ketogenic diet (KD) has recently been reported. We asked whether this diet would have deleterious effects on normal brain function by evaluating KD-induced biochemical changes in the hippocampus as well as neurobehavioral changes. Rats were randomly assigned to three groups on postnatal day 28 (P28): normal rats fed with a KD qd (daily for 4 weeks, NS+KD) or qod (every other day for 4 weeks, NS+KOD), and normal rats fed with standard normal laboratory diet (NS+ND). Neurobehavioral changes were observed on P35, P42 and P49. The hippocampal mossy fiber sprouting, the expression levels of zinc transporters (ZnTs) and lipid metabolism related genes were detected by Timm staining, real-time RT-PCR and western blot analysis, respectively, on P58. The results revealed that there were no significant differences in the three behavior tests among the three groups. The KD-treated NS+KOD and NS+KD groups showed a significant delay of negative geotaxis reflex on P35, but not on P42 or P49. In the open field test, daily KD treatment only led to a reduction in exploratory activity and increased grooming times but induced no significant changes in the scores of vertical activity or delay time. KD qod treated rats (NS+KOD) displayed a slight delay in the place navigation test on P35 compared with the NS+KD group. There were no significant differences in Timm staining among the three groups. KD treatment induced significantly downregulated mRNA levels of Apoa1, Pdk4, and upregulated expression of ApoE, ANXN7, and cPLA2 when compared with the NS+ND group (except in the case of ApoE in the NS+KOD group). Notably, both the mRNA and protein levels of cPla2 in the NS+KOD rats were significantly downregulated compared with the NS+KD group but still markedly higher than in the NS+ND group. Our data suggest that early-life daily KD treatment in normal rats may have no long-term adverse effects on most neurobehavioral parameters, but minor neurobehavioral damage may still exist. The hippocampal lipid metabolism signaling pathway, especially cPLA2, may be the target of the protective effect of KD on long-term brain injury after developmental seizures.